Pengaruh Komunikasi Interpersonal dan Kualitas Pelayanan Customer Care terhadap Tingkat Kepuasan Nasabah PT Prudential Life Assurance Indonesia Cabang Bandung - Benyamin Franklin Rumapea (Universitas Mercu Buana, 2019)
This study aims to determine the effect of interpersonal communication and service quality through customer care on customer satisfaction. The type of research used is a quantitative methodology with a positivistic approach. Quantitative research requires variables to be measured and hypotheses to be tested. The results of the measurements and tests are explained by causal explanations in general. This research is an explorative causative research that explains the influence of interpersonal communication activities and service quality through customer care on customer satisfaction that comes to Prudential Life Assurance Sales Office in Bandung City